Burning mouth syndrome. A case report from diagnosis to cure - Ioanina Parlatescu; Serban Tovaru; Irina Maria Gheorghiu; Paula Perlea (Amaltea Medical Publishing House, 2022)
Burning mouth syndrome (BMS) is a chronic disease of the oral mucosa characterized by persistent oral pain and no clinical lesions or abnormal biological investigations. This paper reports one case of BMS and discusses the main features of this disease's clinical and therapeutical management. A 60 years old female patient had burning sensation on the left lateral border of the tongue for 2.5 years. Local and systemic investigations found no abnormalities. The therapy included local and general medication and the symptoms were remitted. This case report highlights the heterogeneity of BMS, the associated comorbidities, and the evolution of symptoms from diagnosis to cure.